UMP researchers invented ‘MHeLFAGV’ – a forklift that could lift and move loads of more than 50 kg - UMP, PNC (2019)
Concerned over problems faced by the industries relating to material handling equipment, a group of University Malaysia Pahang (UMP) researchers came up with a vehicle that could lift steel roll, weighing between 50kg and 60kg, from a relatively narrow factory store to the inspection room in not more than 20 minutes.